Plasma Lectin Pathway Complement Proteins in Patients With COVID-19 and Renal Disease - Medjeral-Thomas, Nicholas R.; Troldborg, Anne; Hansen, Annette G.; Gisby, Jack; Clarke, Candice L.; Prendecki, Maria; McAdoo, Stephen P.; Sandhu, Eleanor; Lightstone, Liz; Thomas, David C.; Willicombe, Michelle; Botto, Marina; et al. (Frontiers in Immunology, 2021)
We do not understand why non-white ethnicity and chronic kidney disease increase susceptibility to COVID-19. The lectin pathway of complement activation is a key contributor to innate immunity and inflammation. Concentrations of plasma lectin pathway proteins influence pathway activity and vary with ethnicity. We measured circulating lectin proteins in a multi-ethnic cohort of chronic kidney disease patients with and without COVID19 infection to determine if lectin pathway activation was contributing to COVID19 severity. We measured 11 lectin proteins in serial samples from a cohort of 33 patients with chronic kidney impairment and COVID19. Controls were single plasma samples from 32 patients on dialysis and 32 healthy individuals. We demonstrated multiple associations between recognition molecules and associated proteases of the lectin pathway and COVID-19, including COVID-19 severity. Some of these associations were unique to patients of Asian and White ethnicity. Our novel findings demonstrate that COVID19 infection alters the concentration of plasma lectin proteins and some of these changes were linked to ethnicity. This suggests a role for the lectin pathway in the host response to COVID-19 and suggest that variability within this pathway may contribute to ethnicity-associated differences in susceptibility to severe COVID-19.